FOURNIERS SYNDROME: USUAL CURATIVE X CURATIVE WITH HONEY ASSOCIATED WITH DRUG THERAPY, SÃO PAULO, SP, 2005 TO 2007. ABSTRACT (Fiep Bulletin - online, 2011)
Fournier's syndrome, a rare disease that starts with an infection and necrotizing process of subcutaneous tissue, may have different origins, urogenital, anorectal and skin and were due to diseases arising from those areas. The infection is polymicrobial, caused by the synergism between bacteria. Signs and symptoms are pain, swelling, erythema, crackle and tissue necrosis of the fascia, which in some cases appears later fever and purulent secretion foul-smelling abscess already formed in the initial process. The treatment is based on the stabilization of the patient, the surgical debridement and drainage of the area involved and administration of broad spectrum antibiotics, and a cephalosporin 3rd generation or penicillin, an aminoglycoside or metronidazole for anaerobes. The dressing of the site is essential after debridement to remove pus, fibrin tissue and aids in the healing process. Many authors indicate the dressing with honey on the spot and an adjunct to treatment, and has proved effective in helping control swelling and inflammation, death of pathogenic bacteria, debridement of necrotic spots and better wound healing, but this was not takes place in Brazil. The objective of this study was to collect and monitor cases of patients affected by Fournier's syndrome and to verify the therapeutic activity of honey as an adjunct to healing associated with drug treatment. Among the eight cases studied, the data suggest that the use of honey dressings on patients with this syndrome Fournier, reduces the use of antibiotics in terms of asset type and class, suggest that the length of stay and cost of treatment of patients can be reduced if the condition is diagnosed quickly and if used honey as an adjunct to healing.
Keywords: Syndrome Fournier; Fournier's gangrene; topics with honey dressings